FORMATION OF PROFESSIONAL COMPETENCE OF FUTURE TEACHERS OF MATHEMATICS IN THE CONDITIONS OF DIGITALIZATION OF HIGHER EDUCATION - Таточенко, Володимир (SWorldJournal, 2024)
The article specifies the theoretical foundations of the formation of professional competence of future mathematics teachers. The views of scientists on the interpretation of the concepts "professional training of a mathematics teacher", "competence", "p